Two Decades in the Journey of Al-Kindy College Medical Journal: Key Barriers, Achievements, and Prospects - Al-Mendalawi, Mahmood D. (AL-Kindy College Medical Journal, 2022)
Apart from graduating five-star doctors, a particular medical college has the mission to motivate and offer researchers the opportunity to publish high-quality researches on various health problems and disseminate updated medical knowledge to a wide range of local and international readers. This could be accomplished by establishing a medical journal and releasing issues regularly